Encapsulation by electrospray coating atomization of probiotic strains. (February 2017) - Librán, C.M.; Castro, S.; Lagaron, J.M.
Abstract: A new encapsulation method termed electrospray coating atomization (ECA) is presented here for the first time as a new encapsulation concept to enhance the viability of dry powders in general and of freeze-dried probiotic strains in particular. A freeze-dried powder of a probiotic strain (~ 10 log cfu/g) was homogeneously electrospray coated with ultrafine particles of different food hydrocolloids of permitted use in supplemented food and nutraceutical products. The water soluble polymer polyvinylpyrrolidone (PVP) was included in the study as reference pharma permitted encapsulation material. The protected microorganisms were stored at different conditions for periods between 10 and 700 days. Significant differences were found during storage at most of the assayed stressing conditions when compared to the freeze-dried uncoated powder. The results show significantly enhanced comparative survivability of the encapsulated material over time after more than one year at room temperature and 23% RH, especially for whey protein concentrate (WPC), resistant maltodextrin (Fibersol) and PVP. The protective effect of WPC, Fibersol and PVP at 37 °C and 23% RH was also demonstrated. Industrial relevance: Electrospray coating atomization (ECA) is proposed as a new processing methodology for the protection of dry forms of probiotics and in general for the protection of functional/active/bioactive added value ingredients used in the food industry. Since the technology is currently in the process of being scaled up it seems of great significant relevance to an industrial level in order to stabilize or further stabilize existing powder form formulations. Highlights: A new encapsulation method termed electrospray coating atomization (ECA) has been successfully developed. Different food hydrocolloids and PVP were tested as encapsulating agents. ECA protected bacteria had better viability during storage when compared to freeze-dried bacteria. WPC exhibited the most protective effect against humidity after 600 days of storage.